INFLUENCE OF PROCESSING ON PHYSIOCHEMICAL, NUTRITIONAL AND PHYTOCHEMICAL COMPOSITION OF CARISSA SPINARUM (KARONDA) FRUIT - Chauhan, Ambika; Tanwar, Beenu; Arneja, Intelli (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: In this study, the effects of three different processing methods, sun drying, freezing, microwave drying, and fresh fruits of Carissa spinarum in terms of physical, nutritional and phytochemical composition have been studied. Methods: These local variety of fruits were selected from Himachal (India). These fruits were obtained fresh, cleaned, and washed prior to selected techniques. Results: As we see from, the results in Tables showed that drying techniques improved the protein, carbohydrates, ash content, dietary fiber (neutral detergent fiber, acid detergent fiber, cellulose, hemicelluloses, and lignin), total phenol, antioxidant activities, and mineral content. Drying destroyed total flavonoids, tannin, alkaloid, and anthocyanin content. Conclusions: The findings of the research is clearly indicated that some processing methods are proved good for more nutrient retension as compared to others. This study aim to make consumers aware about the effects of processing methods on nutritional value of fruits and study will help people to generate awareness for the intake of these underutilized fruits in their daily diet increase nutritional status in a better way. Keywords: Sun drying, Freezing, Microwave drying, Carissa spinarum.